THE JUSTICE EROSION OF THE IMPOSITION OF ECONOMIC SANCTIONS IN INTERNATIONAL LAW ENFORCEMENT - Gonzales, Marcellino (Badan Pembinaan Hukum Nasional Kementerian Hukum Republik Indonesia, 2024)
After the COVID-19 pandemic occurred some time ago, which paralyzed all aspects of life in the world, not long after, in 2022, an armed conflict occurred involving Russia and Ukraine, which continues to this day. In line with the armed conflicts that have emerged recently, various international economic sanctions targeting warring countries have begun to be imposed. Ironically, instead of weakening the sanctioned country’s defense, the embargo imposed by a sanctioned country on a particular country turns out to have a harsh impact on all aspects of the lives of its civilians, both the sanctioned country and the sanctioning country in several cases. The imposition of various international sanctions is one of the causes. Reflecting on this, the author will analyze more deeply what is the concept of international economic sanctions. Secondly, does the imposition of international economic sanctions fulfill the basic concept of implementing economic sanctions today? The method used in this paper is qualitative research with normative juridical methods. From the discussions, It can be concluded that economic sanctions are the withdrawal of trade habits and financial relations for foreign and security policy. Sanctions can be comprehensive, prohibiting commercial activity against entire countries. However, there is uncertainty regarding the length of economic sanctions imposed on a country, which causes prolonged suffering for the people of a country. Apart from that, the dominance of countries that have significant political and economic power has led to the emergence of abuse of the imposition of economic sanctions themselves. The article recommends that countries should compose the development of international legal rules originating from international agreements that focus on three main things: management processes, and results that lead to sustainable benefits based on the principle of equality in creating agreements between countries.